Research Progress on the Antiemetic Effect of Traditional Chinese Medicine Against Chemotherapy-Induced Nausea and Vomiting: A Review - Zhao, Yao-Zhong; Dai, Yong-Zhao; Nie, Ke (Frontiers in Pharmacology, 2022)
Chemotherapy-induced nausea and vomiting (CINV), a common side effect in antineoplastic treatment, dramatically decreases the quality of life as well as the compliance of cancer patients. Although numerous antiemetic agents have been used for CINV treatment, its adverse reactions as well as its inadequate control toward delayed emesis still limit its clinical usage. Traditional Chinese medicine (TCM), with more than 3,000 years of practical history in Asia, has been successfully applied to mitigate chemotherapy-induced side effects. Growing attention is drawn to the antiemetic effect of TCM against CINV due to its promising therapeutic property and higher safety recently. In this review, we summarize the classic antiemetic TCM-based treatment and its mechanisms, so as to provide a theoretical basis for further investigations of TCM against CINV in the future.